Government policy and critical success factors of small businesses in Singapore - Siow, Harold Song Teng (Cambridge Scholars Publishing, 2011)
One of the main economic players responsible for Singapore's economic success is its small and medium-sized enterprises or SMEs. Their overall success has helped propel the country and its people forward. From economic policies to politics, Singapore is a planned and regulated economy.